(untitled) (Archive of Conferences, 2022)
This article discusses the basic elements of landscape architecture and landscape design devices, landscape design devices and their architecture is one of the most important areas of landscape architecture related to creating an aesthetic, easy-to-use, scenic and healthy functional environment.